Overhauling Management of Agriculture to Improve Sector Performance : Synthesis Report - World Bank (World Bank, Washington, DC, 2020)
The essence of good government is doing the right things, in the right way, in the right place. This functional review focuses on those three issues, first asking whether there are tasks that do not need to be done at all, or at least not by a government ministry, then asking whether necessary tasks can be done better and more efficiently, and finally asking what the best institutional location and structure is to carry out those tasks.